(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The concept of inclusive education (IE) suffered many challenges some of which have been linked to teachers’ lack of knowledge and understanding to teach in an IE environment. In Samoa, it is now almost two decades since the inclusive education (IE) phenomenon has been introduced into its education system, however it is still not clear how teachers feel about their preparation to teach in an IE environment. This qualitative research examined teachers’ views concerning their teacher preparation for IE. Using an open ended questionnaire, data was gathered from 94 pre and in- service primary school teachers who were in 2022 trained within the faculty of education (FOE) at the National University of Samoa. Findings indicated that teachers needed adequate IE courses to prepare them to teach in an IE classroom as the single IE course that is currently offered by the faculty is not sufficient to provide them with the requisite knowledge and skills to teach in an IE environment. Findings also suggested that limited IE knowledge suffered from the absence of an IE program and lack of opportunity for teachers to practice learned skills within an IE environment which in turn affected their confidence to teach in such context. This has greater implication on teacher training preparations, hence the need for the training institution to develop programs in IE so teachers are well equipped to work in such context is very crucial.